Dysregulation of MS risk genes and pathways at distinct stages of disease. Issue 3 (May 2017) - Srinivasan, Sundararajan; Di Dario, Marco; Russo, Alessandra; Menon, Ramesh; Brini, Elena; Romeo, Marzia; Sangalli, Francesca; Costa, Gloria Dalla; Rodegher, Mariaemma; Radaelli, Marta; Moiola, Lucia; Cantarella, Daniela; et al.
Abstract : Objective: To perform systematic transcriptomic analysis of multiple sclerosis (MS) risk genes in peripheral blood mononuclear cells (PBMCs) of subjects with distinct MS stages and describe the pathways characterized by dysregulated gene expressions. Methods: We monitored gene expression levels in PBMCs from 3 independent cohorts for a total of 297 cases (including clinically isolated syndromes (CIS), relapsing-remitting MS, primary and secondary progressive MS) and 96 healthy controls by distinct microarray platforms and quantitative PCR. Differential expression and pathway analyses for distinct MS stages were defined and validated by literature mining. Results: Genes located in the vicinity of MS risk variants displayed altered expression in peripheral blood at distinct stages of MS compared with the healthy population. The frequency of dysregulation was significantly higher than expected in CIS and progressive forms of MS. Pathway analysis for each MS stage–specific gene list showed that dysregulated genes contributed to pathogenic processes with scientific evidence in MS. Conclusions: Systematic gene expression analysis in PBMCs highlighted selective dysregulation of MS susceptibility genes playing a role in novel and well-known pathogenic pathways.